The Effect Of Living Money and Lifestyle On Student Financial Management Economic Education - Sarwono Tumangger; Fachruddiansyah Muslim; Romi Kurniadi (Jurnal Smart: Sosial Ekonomi Kerakyatan, 2023)
This study aims to test and describe how significant the influence of the interaction of differences in pocket money and lifestyle is on the financial management of 2019-2020 Economics Education Students at the University of Jambi. The research was conducted at the Teaching and Education Faculty, Jambi University, April-May 2023 by distributing a research questionnaire. This study uses an approach with a quantitative descriptive research type with the classical assumption test method with analysis Two Way Anova to look for differences and influences between variables, the F test, the marginal average test and the coefficient of determination. The results show that there is a significant difference between pocket money and lifestyle on the financial management of 2019-2020 Economics Education Students. The results show significance (0.005 <0.05) with Fcount > Ftable (3.946 > 3.07). The coefficient of determination (R) is 0.561 or 56%, or the meaning of this value indicates that 56% of financial management is influenced by pocket money and lifestyle and the remaining 44% is influenced by other independent variables not examined.